Crossing-Duct sign and recurrent pancreatitis: A case report with review of pancreatic embryology - Ilyas, Mohd; Shafi, Fahad; Shabir, Sadia; Gojwari, Tariq (Ibnosina Journal of Medicine and Biomedical Sciences, 2017)
Pancreatic divisum is a congenital anomaly of the pancreatic ductal system wherein the dorsal duct system fails to fuse with ventral ductal system and results in the major pancreatic drainage through the minor duodenal papilla and minor drainage through the major duodenal papilla. It is a rare cause of recurrent pancreatitis.
Keywords: Crossing-duct sign; pancreatic divisum; recurrent pancreatitis